Straits settlements laws [1908-1919] (Petaling Jaya : Arkib Negara)
Mengandungi vol. III 1908-1912. Vol. IV 1913-1919 no. 134-174 1908 1919. The Laws of the Straits Settlements Relating to Shipping and Ports. (1920 Revision) no. 28, 42, 69 112 and 125. Termasuk ordinan-ordinan no. 125 Merchant shipping (Ord. no. XXXII of 1910); Ord. no. 126 Public Officers; Guarantee Fund (Ord. no. II of 1911); Ord. no. 127 Labuan (Ord. no. III of 1911); Orde. no. 129 Traction engines and Motorcars (Ord. no. XIX of 1911) Ord. no. 135 Municipal (Ord. no. IX of 1913); Ord. no. 136 Arms and explosives (Ord. no. IX of 1913); Ord.no. 145 Life assurance Companies (Ord. no. XXXIII of 1914); Ord. no. 153 Banishment (Ord. no. 136 Arms and Explosives (Ord. no. IX of 1913); Ord. no. 145 Life Assurance Companies (Ord. no. XXXIII of 1914); Ord. no. 153 Banishment (Ord. XVIII of 1915); Ord. no. 158 Tobacco Duties (Ord. no. XIV of 1916); Ord. No. 164 Fire Insurance Companies (Ord. no.XXY of 1917.